2016
DOI: 10.1016/j.neuropsychologia.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of the relationship between crowding and reading: A neurodegenerative approach

Abstract: We have previously documented two patients (FOL and CLA) with posterior cortical atrophy who achieved accurate and rapid reading despite deficits in ten measures of visual processing, with two notable exceptions: (1) a measure of visual acuity, (2) a measure of visual crowding. Subsequent longitudinal investigation of these patients was carried out, involving annual tests of early visual, visuoperceptual and visuospatial processing and assessment of reading ability. Follow-up assessments identified the evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…A small number of longitudinal case reports and case series have described the clinico-radiological progression of the condition (Ross et al , 1996; Goethals and Santens, 2001; Giovagnoli et al , 2009; Kennedy et al , 2012; Chang et al , 2015; Crutch et al , 2017) or the development of specific cognitive deficits [e.g. dyslexia and excessive visual crowding (Yong et al , 2016), dysgraphia (Primativo et al , 2017)]. The only previous longitudinal group study found comparable rates of widespread grey matter loss in patients with PCA and typical Alzheimer’s disease with a mean disease duration of 5 years, but participant numbers were small (17 PCA, 16 typical Alzheimer’s disease) and the time window limited (1-year interval) (Lehmann et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A small number of longitudinal case reports and case series have described the clinico-radiological progression of the condition (Ross et al , 1996; Goethals and Santens, 2001; Giovagnoli et al , 2009; Kennedy et al , 2012; Chang et al , 2015; Crutch et al , 2017) or the development of specific cognitive deficits [e.g. dyslexia and excessive visual crowding (Yong et al , 2016), dysgraphia (Primativo et al , 2017)]. The only previous longitudinal group study found comparable rates of widespread grey matter loss in patients with PCA and typical Alzheimer’s disease with a mean disease duration of 5 years, but participant numbers were small (17 PCA, 16 typical Alzheimer’s disease) and the time window limited (1-year interval) (Lehmann et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…newspaper headlines rather than smaller words); and letters appearing to move or merge [35,65,68]. Such loss is predominantly considered to reflect peripheral alexia, variously described as 'apperceptive' [68] or 'crowding dyslexia' [83,84]. Eye-tracking recordings emphasise inefficient fixations and saccades accompanying inaccurate reading [32], with patient reports of static text appearing to move possibly relating to fixation instability [41,78].…”
Section: Readingmentioning
confidence: 99%
“…Likewise, fMRI has revealed that activation within the ventral visual regions is related to facial and object recognition, while that in dorsal areas is related to motion and gestalt perception (29, 30). Visual word processing is a function of the ventral visual stream, and patients with PCA have been reported to exhibit functional deficits in word processing that are seen in reading disorders (31). Although weakened cortical peripheral visual field functions are similar to peripheral visual deficits seen in behavioral pathology, disruption of the dorsal stream has been suggested to result from impaired interconnectivity of feed-forward and -backward pathways.…”
Section: Pca Based On Posterior Cerebral Changesmentioning
confidence: 99%